Estimate of propulsive force in front crawl swimming in young athletes - Santos, M. A.; Barbosa Jr., M. L.; Melo, W. V.; Veronese da Costa, A.; Costa, M. C. (Open Access Journal of Sports Medicine, 2012)
Background: Improvement in swimming performance involves the dynamic alignment of the body in liquid, technical skill, anthropometric characteristics of athletes, and the ability to develop propulsive force. The aim of this study was to assess the relationships between the propulsive force during swimming and arm muscle area (AMA) and propose an equation to estimate the propulsive force in young swimmers by measuring their AMA. Methods: Study participants were 28 male swimmers (14 ± 1.28 years) registered in the Brazilian Federation of Aquatic Sports. Their AMA was estimated by anthropometry and skinfold measurement, and the propulsive force of their arm (PFA) was assessed by the tied swimming test. The Durbin-Watson (DW) test was used to verify residual independence between variables (PFA and AMA). A Pearson correlation investigated potential associations between the variables and then a linear regression analysis was established. The Bland-Altman method was used to compare the values found between PFA and propulsive force-estimated (PFE). A paired Student's t-test was used to analyze the difference in PFE with and without the constant and the coefficient of variation (CV) to estimate the magnitude of a real change between these forces. Results: There was a significant positive correlation between the variables AMA and PFA (r = 0.68, P < 0.001). The linear regression showed a value of R² = 0.470. There were no significant differences when comparing PFA and PFE (95% confidence interval: -8.903 to 9.560 kgf). To verify if there was a correlation between these variables, a new linear regression analysis found a value of R2 = 0.668, which confirms an equivalence between PFA and PFE, as CV showed 4% of magnitude. Conclusion: The results of this study suggest the existence of a relationship between levels of PFA and muscle mass, however, this relationship becomes more evident the longer the AMA, which allows the development of an equation to estimate the propulsive force of young swimmers.